2004
DOI: 10.1111/j.1365-2095.2004.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and metabolism of a particulate form of ascorbic acid by Artemia nauplii and juveniles

Abstract: A study was conducted to establish whether a particulate form of ascorbic acid (AA), ascorbyl‐2‐phosphate (A2P), could be used to enrich Artemia. In the first experiment, we examined the efficiency of A2P conversion to and maintenance of AA by juvenile Artemia (1.5 mm, 5‐day‐old) held at 9000 L−1 and 28 °C for 24 h. Maximal uptake and assimilation was >10 000 μg AA g−1 dry weight (dw) (representing >1%Artemia dw) at enrichment rates of ≥1.2 g A2P L−1. In the second experiment, a similar biomass of instar II/II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
1
9
1
Order By: Relevance
“…This suggested that the best enrichment method of AMP-Mg in Artemia nauplii was achieved at a dose of 0.9 g/L for 6 h (P<0.05) and this result was used as the protocol for humpback grouper larval rearing. The result in the present study was different from that reported by Smith et al (2004). Their study showed that the maximum enrichment using ascorbyl-2-phosphate was attained at rates of 8 1.2 g/L for 24 h giving a 60-fold increase in Artemia nauplii AA levels.…”
Section: Artemia Enrichmentcontrasting
confidence: 99%
“…This suggested that the best enrichment method of AMP-Mg in Artemia nauplii was achieved at a dose of 0.9 g/L for 6 h (P<0.05) and this result was used as the protocol for humpback grouper larval rearing. The result in the present study was different from that reported by Smith et al (2004). Their study showed that the maximum enrichment using ascorbyl-2-phosphate was attained at rates of 8 1.2 g/L for 24 h giving a 60-fold increase in Artemia nauplii AA levels.…”
Section: Artemia Enrichmentcontrasting
confidence: 99%
“…For Artemia , its gut contents were evacuated during the first 3 h at the highest concentrations (1000 and 1500 mg/kg AMP‐Na/Ca) and over a period of 3–6 h at the lowest concentration (500 mg/kg), which supports the findings of Smith et al (, , ) in juvenile Artemia 6 h after oil enrichment and fasting. The understanding of the rate of incorporation and loss of L‐AA and AMP‐Na/Ca in Artemia nauplii and metanauplii during both enrichment and the subsequent fasting has assisted in the development of feeding regimes that target crustaceans and fish (Evjemo et al ; Smith et al ).…”
Section: Discussionsupporting
confidence: 86%
“…In recent years, the rearing of new aquaculture species with specific life stage requirements has required diversifying the use of Artemia by including live juvenile and adults as well as frozen or freeze-dried AB (Lim et al 2002;Smith et al 2002Smith et al , 2004a. The ability of Artemia to metabolize and store specific biochemical substances (Sorgeloos et al 1998;Narciso et al 1999;Smith et al 2002) while suffering no obvious detrimental physiological effects enables their use as a vehicle for the delivery of chemotherapeutics, including L-AA.…”
Section: Discussionmentioning
confidence: 99%
“…1980). It is possible to boost the AA concentration in juvenile Artemia to greater than 10 000 μ g g −1 dry weight (dw) within 24 h using an ascorbyl‐2‐phosphate (A2P) particulate enrichment (Smith et al . 2004).…”
Section: Introductionmentioning
confidence: 99%